2003
DOI: 10.1093/carcin/bgg031
|View full text |Cite
|
Sign up to set email alerts
|

p53 responsive nucleotide excision repair gene products p48 and XPC, but not p53, localize to sites of UV-irradiation-induced DNA damage, in vivo

Abstract: The p53 tumor suppressor gene is an important mediator of the cellular response to ultraviolet (UV)-irradiation-induced DNA damage and affects the efficiency of the nucleotide excision repair (NER) pathway. The mechanism by which p53 regulates NER may be through its ability to act as a transcription factor, and/or through direct interactions with damaged DNA or the repair machinery. p53 has been shown to regulate the expression of the DDB2 gene (encoding the p48 protein) and the XPC gene, two important compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 49 publications
0
44
1
Order By: Relevance
“…This is not surprising as the underlying mechanism to initiate productive repair is based on the binding of the heterodimeric protein to DNA damage. Earlier studies have reported that DDB2 is required for the recruitment of exogenously transfected DDB1 to the local UV-induced damage sites (33). Here, we tested the chromatin binding of endogenous DDB1 protein following UV irradiation and show that almost all the native DDB1 in the nuclei translocates from loosely bound to a tightly bound chromatin form upon UV irradiation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This is not surprising as the underlying mechanism to initiate productive repair is based on the binding of the heterodimeric protein to DNA damage. Earlier studies have reported that DDB2 is required for the recruitment of exogenously transfected DDB1 to the local UV-induced damage sites (33). Here, we tested the chromatin binding of endogenous DDB1 protein following UV irradiation and show that almost all the native DDB1 in the nuclei translocates from loosely bound to a tightly bound chromatin form upon UV irradiation.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have shown that DDB1 is not needed for the repair of damage in the NER system reconstituted in vitro (19,20). However, in vivo studies have shown that ectopically expressed DDB1 could be recruited to the damage sites following UV irradiation (33), suggesting that DDB1, as a subunit of DDB, is capable of binding to the damaged sites. In this study, we investigated the chromatin binding and UV-induced translocation of DDB1 by using cellular fractionation and immunoblot analysis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Using local irradiation, an elegant technique that allows visualization of events occurring in UVC-irradiated zones of the nuclei (Moné et al, 2001), we show that PARP activation occurs at the site of UVC exposure as rapidly as reported accumulation of p48/UV DNA damage binding protein 2 (UV-DDB2) (Fitch et al, 2003;Tang and Chu, 2002). Since DDB protein complex is thought to be responsible for initial recognition of CPD damage (Hanawalt, 2002;Tang and Chu, 2002), our results indicate that PARP Journal of Cell Science 118 (3) activation occurs concomitant with DDB2 binding to the direct DNA lesions and occurs prior to the start of NER process at the damaged site.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper Wang et al (2004) demonstrated in human cells that DDB2 is a downstream effector of p53, which recognizes CPDs and can stimulate XPC recruitment and binding at the site of damage (Fitch et al, 2003a). This provides a clear explanation for the defect in global repair in p53-deficient human cells: lack of ChIP assay for E2F1-3.…”
Section: Ddb2 Is Not Activated By P53mentioning
confidence: 99%